2017
DOI: 10.3390/ijgi6030063
|View full text |Cite
|
Sign up to set email alerts
|

An Improved DBSCAN Algorithm to Detect Stops in Individual Trajectories

Abstract: Abstract:With the increasing use of mobile GPS (global positioning system) devices, a large volume of trajectory data on users can be produced. In most existing work, trajectories are usually divided into a set of stops and moves. In trajectories, stops represent the most important and meaningful part of the trajectory; there are many data mining methods to extract these locations. DBSCAN (density-based spatial clustering of applications with noise) is a classical density-based algorithm used to find the high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…The laser ranging data are segmented into different clusters using DBSCAN. 49 The two closest clusters at the adjacent time are regarded as the same obstacle, and the distance between the two clusters is used to estimate the laser-based velocity. Second, we perform velocity matching to compute the similarity between phase-based velocity and laser-based velocity.…”
Section: Researchersmentioning
confidence: 99%
“…The laser ranging data are segmented into different clusters using DBSCAN. 49 The two closest clusters at the adjacent time are regarded as the same obstacle, and the distance between the two clusters is used to estimate the laser-based velocity. Second, we perform velocity matching to compute the similarity between phase-based velocity and laser-based velocity.…”
Section: Researchersmentioning
confidence: 99%
“…Empirical results presented in this paper are close to the experimental results obtained in the works [1] and [3] in which it was shown that the k-MXT algorithm is applicable to the solution of the clusterization problem and produces clusters which are comparable to the clusters obtained by DBSCAN algorithm. An extended version of DBSCAN algorithm was examined in [4] to detect stops in individual trajectories using GPS data. The paper [5] proposes a novel niche genetic algorithm (NGA) with density and noise for K-means clustering and apply the algorithm on taxi GPS data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Issues concerning how to mine the hidden information and understand the meaning of these states, as well as how the information of trajectories can be employed in urban development have become research hotspots. Therefore, a great quantity of clustering-based approaches was presented to describe states of the city, which utilized characteristics and trajectory pattern clustering of GPS data [1,6,[9][10][11][12][13][14][15][16]. For example, Reference [10] presented a density-based line segments trajectories clustering algorithm that was based on a partition and group framework.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [11] presented a scalable and fast density clustering algorithm that was based on big data computing. Also, the authors of Reference [16] presented an improved density-based algorithm that was to be used for stops clustering in trajectories. In particular, work in Reference [17] proposed an anisotropic (angle-based standard deviation) density-based clustering algorithm, which was used to discover spatial point patterns with noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation